2016
DOI: 10.1016/j.ijscr.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Isolated omental metastasis of renal cell carcinoma after extraperitoneal open partial nephrectomy: A case report

Abstract: HighlightsThis is the first reported case of metachronous isolated omental metastasis of an initially T1 clear-cell RCC.Noninvasive diagnostic studies may not differentiate sarcoidosis from metastatic spread of RCC.Sarcomatoid paraneoplastic syndrome was triggered by the formation of omental metastatic deposit in this patient who have been previously diagnosed with sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These can be classified into three subcategories, i.e. first as presentation with disseminated peritoneal disease, second as recurrence after initial nephrectomy [ 20 ] and third, most common nowadays, as port site and omental mets after the laparoscopic excision of renal masses. Stavropoulos et al reported a case who presented with peritoneal metastasis and noted that the incidence of peritoneal metastasis in renal cell carcinoma is about 1% at autopsy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These can be classified into three subcategories, i.e. first as presentation with disseminated peritoneal disease, second as recurrence after initial nephrectomy [ 20 ] and third, most common nowadays, as port site and omental mets after the laparoscopic excision of renal masses. Stavropoulos et al reported a case who presented with peritoneal metastasis and noted that the incidence of peritoneal metastasis in renal cell carcinoma is about 1% at autopsy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was totally asymptomatic. While metastasis of RCC in the liver and mediastinum is frequently observed, omental metastasis is very rare [ 16 ]. Metastasis to the thyroid is relatively rare, despite its rich blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Few recent studies have evaluated the role of FDG-PET/CT in response to tyrosine kinase inhibitors in metastatic RCC. [19]…”
Section: Discussionmentioning
confidence: 99%